1975
DOI: 10.1007/bf01070840
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the jejunum associated with nontropical sprue

Abstract: A patient with a thirty-year history of celiac disease, developed malabsorption and ultimately intestinal obstruction. He failed to respond to a strict gluten-free diet, steroids, and antibiotics. Postmorten examination revealed primary adenocarcinoma of the small bowel. The relationship between adenocarcinoma of the jejunum and celiac disease is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Cooper and associates [21] have cogently summarized the reasons for the increased incidence of malignant change and feel that the possibility of lymphoma should be considered in patients who present with either celiac disease m midlife or who deteriorate for no apparent reason after a period of stability on a gluten-free diet. Although the foregut and hindgut are the 2 common sites for adenocarcinoma developing in association with celiac disease [21], midgut lesions have also been documented [9,22]. Intestinal tymphoma has been reported as a complication of immune deficiency states [23] and it is tempting to speculate on the association between the use of immunosuppressants and lymphoma in 1 of our patients who had undergone a live donor renal transplant 12 years prior to presentation.…”
Section: Discussionmentioning
confidence: 83%
“…Cooper and associates [21] have cogently summarized the reasons for the increased incidence of malignant change and feel that the possibility of lymphoma should be considered in patients who present with either celiac disease m midlife or who deteriorate for no apparent reason after a period of stability on a gluten-free diet. Although the foregut and hindgut are the 2 common sites for adenocarcinoma developing in association with celiac disease [21], midgut lesions have also been documented [9,22]. Intestinal tymphoma has been reported as a complication of immune deficiency states [23] and it is tempting to speculate on the association between the use of immunosuppressants and lymphoma in 1 of our patients who had undergone a live donor renal transplant 12 years prior to presentation.…”
Section: Discussionmentioning
confidence: 83%
“…Such an incidence of malignancy is, of course, much higher than that expected from any control population. Between 1941 and1975, of the total of 97 deaths, 37 have been due to malignant disease, leaving little doubt that, in this series of 202 patients, there has been an increase in deaths from cancer, particularly reticulum cell sarcoma and gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Thus the reports of the 15 patients with adenocarcinoma of the jejunum have been reviewed by Petreshock et al (1975), while Harris et al (1967) found that the incidence ofgastrointestinal carcinoma was significantly increased, particularly oesophageal carcinoma in men.…”
mentioning
confidence: 99%
“…Numerous condition:, arc predisposing facto rs fo r sma ll bowel cancer. C cliac sprue has been associated with lymphoma ( 17) anJ has been implicated in the pathogenesis of adenocarcinomas (18). Dermariris herpetiformis has a lso been assoc ia ted with a disproportionate n umber of small bowel ad enocarc inom as ( 19).…”
Section: Small Bowel Tumoursmentioning
confidence: 99%